MOF (at) SAC adsorbent with hierarchical pore structure and multiple Lewis acid sites and preparation method of MOF (at) SAC adsorbent

By growing sulfonic acid group-modified MOF on spherical activated carbon in situ, forming a multi-stage pore structure and a MOF@SAC adsorbent with multiple Lewis acid sites, the problem of insufficient performance in removing trace ammonia is solved, and efficient NH3 adsorption effect is achieved.

CN119838576APending Publication Date: 2025-04-18SCI & TECH QINGKE (BEIJING) TECH CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202510109482.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-23
Publication Date
2025-04-18

AI Technical Summary

Technical Problem

The prior art is difficult to effectively remove trace amounts of ammonia (NH3) during semiconductor manufacturing, and the adsorption performance of traditional activated carbon is limited and difficult to meet the requirements of high-purity air.

Method used

Ultra-high cross-linked styrene resin microspheres were reacted with polychlorinated alkanes to prepare ultra-high cross-linked styrene resin (HPS), and then high-temperature heat treatment was used to obtain spherical activated carbon (SAC). Finally, the sulfonic acid group-modified metal organic frame material (MOF) was grown on the SAC in situ to form a MOF@SAC adsorbent with a multi-stage pore structure and a multi-Lewis acid site.

Benefits of technology

It significantly improves the adsorption filtration performance of NH3, improves the adsorption capacity and diffusion rate, and is suitable for industrial-scale production.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119838576A_ABST
    Figure CN119838576A_ABST
Patent Text Reader

Abstract

The invention discloses an MOF (at) SAC adsorbent with a hierarchical pore structure and multiple Lewis acid sites and a preparation method of the MOF (at) SAC adsorbent, and relates to the technical field of adsorbents. Step S2, preparing spherical activated carbon; step S3, preparation of a functional ligand; and S4, in-situ growth of the MOF is carried out. The MOF (at) SAC adsorbent with the hierarchical pore structure and the multiple Lewis acid sites, disclosed by the invention, is high in adsorption efficiency, adjustable in structure function and easy to process and form.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of adsorbents, and in particular to a MOF@SAC adsorbent having a multi-level pore structure and multiple Lewis acid sites and a preparation method thereof. Background Art

[0002] In modern semiconductor manufacturing, the clean room environment is crucial to the quality of the process. Trace amounts of ammonia (NH3) can have a serious impact on the surface of silicon wafers and process equipment. NH3 can react chemically with the surface of silicon wafers, resulting in reduced image resolution in the photolithography process, defects in the thin film deposition process, and even adverse effects on the electrical performance of the device. Therefore, how to efficiently remove ammonia has become an important technical problem in semiconductor clean room management.

[0003] Activated carbon is widely used in the adsorption of gaseous pollutants due to its high specific surface area and developed pore structure. For example, the Chinese invention patent with the authorization announcement number CN111533127B discloses an activated carbon that can adsorb a variety of VOC gases, achieving the goal of comprehensively improving air quality. However, similar traditional activated carbon still has many limitations in practical applications. First, its particle morphology is uneven, and it is easy to produce powder during use, which affects the stability of equipment operation and adsorption performance; in addition, although the pore structure of traditional activated carbon can provide certain adsorption sites, it is still mainly based on physical adsorption mechanism, so the ability to capture trace NH3 is limited; at the same time, although the specific surface area of ​​traditional activated carbon is high, the pore size distribution is uneven, and the micropores are too dense to limit the diffusion of gas molecules, further reducing the adsorption efficiency. In general, traditional activated carbon adsorbents have been difficult to meet the strict requirements for high-purity air in the semiconductor manufacturing process.

[0004] In recent years, metal organic framework materials (MOFs) have shown great application potential in gas adsorption due to their high specific surface area, adjustable pore size and diverse chemical functionalization potential. According to the physicochemical properties of different gas molecules, the selection of metal nodes and organic ligands can be adjusted to make them interact strongly with gas molecules, thereby achieving efficient adsorption. For example, the Chinese invention patent with application publication number CN118185037A discloses a metal organic framework with a large pore size constructed with 1,4-di(1H-pyrazol-4-yl)benzene (H2BDP) as an organic ligand and copper chloride (CuCl2) as a metal node for the adsorption and storage of NH3. However, MOF materials also have significant shortcomings, such as poor chemical stability and possible decomposition in high humidity or highly corrosive environments. In particular, MOFs are usually difficult to directly process into forms suitable for industrial applications, such as particles or films, which restricts their application in actual industrial scenarios.

[0005] In view of this, it is necessary to develop an NH3 adsorbent with high adsorption efficiency, adjustable structure and function, and easy processing to achieve efficient removal of trace NH3. Summary of the invention

[0006] The purpose of the present invention is to provide a MOF@SAC adsorbent with a multi-level pore structure and multiple Lewis acid sites and a preparation method thereof in order to overcome the deficiencies of the prior art. A super-high cross-linking degree styrene resin (HPS) is prepared by subjecting styrene resin (PS) microspheres to a Friedel-Crafts reaction with polychlorinated alkanes, and then a spherical activated carbon (SAC) with a rich pore structure and a high specific surface area is obtained by high-temperature heat treatment. Finally, a functional ligand modified with a sulfonic acid group is used as a reaction precursor to in-situ growth on the spherical activated carbon to obtain a MOF-modified spherical activated carbon (MOF@SAC) with a multi-level pore structure and multiple Lewis acid sites. The MOF@SAC adsorbent provided by the present invention has a multi-level pore structure and a rich specific surface area, and a high-density Lewis acid site is constructed on the MOF structure with transition metals and functionalized ligands, which significantly improves its adsorption and filtration performance for NH3.

[0007] To achieve the above object, the technical solution adopted by the present invention is: a method for preparing a MOF@SAC adsorbent having a multi-level pore structure and multiple Lewis acid sites, comprising the following steps:

[0008] Step S1, preparation of ultra-high cross-linked styrene resin: using polystyrene microspheres as a precursor resin, immersing them in polychlorinated alkanes for 6-24 hours; then, adding a catalyst in batches under magnetic stirring at 300-1000 rpm in an ice-water bath, and maintaining stirring in the ice bath for 4-12 hours; after the reaction is completed, repeatedly washing with dichloromethane until the effluent becomes clear, then extracting with an organic solvent for 6-18 hours, and finally washing with deionized water until the eluent is neutral, to obtain an ultra-high cross-linked styrene resin;

[0009] Step S2, preparation of spherical activated carbon: moving the ultra-high cross-linked styrene resin prepared in step S1 into a tubular furnace for high-temperature heat treatment to obtain spherical activated carbon;

[0010] Step S3, preparation of functionalized ligand: first, add organic ligand and sulfonation reagent into a three-necked flask, and react for 4-12 hours under magnetic stirring; then, slowly pour the reaction solution into a mixture of ice and water to allow the product to precipitate; finally, collect the product by vacuum filtration, and wash it alternately with ethanol and deionized water for 3 times to remove excess acid to obtain a functionalized ligand;

[0011] Step S4, in-situ growth of MOF: First, weigh the metal salt, dissolve it in an organic solvent under magnetic stirring to obtain a metal salt solution; then weigh the functional organic ligand prepared in step S3, dissolve it in an organic solvent under magnetic stirring to obtain a ligand solution; then, the spherical activated carbon prepared in step S2 is uniformly dispersed in the above-mentioned metal salt solution under magnetic stirring; next, under the action of magnetic stirring, slowly add the ligand solution, add a nucleating agent, and react at 60-240°C for 2-36h; finally, after washing and drying, MOF-modified spherical activated carbon MOF@SAC is obtained.

[0012] Preferably, the amount ratio of the polystyrene microspheres, polychlorinated alkanes, and catalyst in step S1 is (20-150) g: (100-600) mL: (10-60) g.

[0013] Preferably, the polychlorinated alkanes in step S1 are one or more of dichloromethane, chloroform, and 1,2-dichloroethane.

[0014] Preferably, the catalyst in step S1 is one or more of anhydrous AlCl3 and anhydrous FeCl3.

[0015] Preferably, the organic solvent in step S1 is any one of methanol, ethanol, N,N-dimethylformamide, and N-methylpyrrolidone.

[0016] Preferably, the high temperature heat treatment in step S2 is specifically as follows: first, under the protection of N2, the temperature is raised to 275-340°C at a rate of 5-7.5°C / min, and maintained at this temperature for 1-1.5h; then, the temperature is raised to 400-480°C at a rate of 7.5-10°C / min, and maintained at this temperature for 2-3h; then, the temperature is raised to 575-625°C at a rate of 10-15°C / min, and maintained at this temperature for 4-6h, and finally, it is naturally cooled to room temperature.

[0017] Preferably, the amount ratio of the organic ligand, the sulfonation reagent, and the ice-water mixture in step S3 is (10-50) g: (20-100) mL: (300-600) mL.

[0018] Preferably, the organic ligand in step S3 is any one of terephthalic acid, 1,4-phthalic acid, and trimesic acid.

[0019] Preferably, the sulfonating agent in step S3 is any one of concentrated sulfuric acid, chlorosulfonic acid, sulfur trioxide, and fuming sulfuric acid.

[0020] Preferably, the ratio of the metal salt to the organic solvent in the metal salt solution in step S4 is (2-20) g: (50-250) mL.

[0021] Preferably, the molar ratio of the functional organic ligand to the organic solvent in the ligand solution in step S4 is (10-80) g: (50-250) mL.

[0022] Preferably, the mass ratio of the metal salt, the functional organic ligand, the spherical activated carbon and the nucleating agent in step S4 is (2-20):(10-80):(20-100):(0-5).

[0023] Preferably, the metal salt in step S4 is any one of zinc salt, cobalt salt, copper salt, iron salt, titanium salt, aluminum salt and zirconium tetrachloride.

[0024] Preferably, the zinc salt is any one of Zn(NO3)2·6H2O, ZnSO4·7H2O, and Zn(CH3COO)2·2H2O; the cobalt salt is any one of Co(NO3)2·6H2O, CoSO4·7H2O, and CoCl2·6H2O; the copper salt is any one of Cu(NO3)2·3H2O, CuCl2, and Cu(CH3COO)2·H2O; the iron salt is any one of Fe(NO3)3·9H2O and FeCl3·6H2O); the titanium salt is any one of TiCl4 and TiOCl2; the aluminum salt is any one of Al(NO3)3·9H2O and AlCl3.

[0025] Preferably, the nucleating agent in step S4 is one or more of hydrogen chloride, sodium hydroxide, polyvinyl alcohol, sodium dodecylbenzene sulfonate, and polyvinyl pyrrolidone.

[0026] Preferably, the organic solvent in step S4 is any one of deionized water, methanol, ethanol, N,N-dimethylformamide, and N,N-dimethylacetamide.

[0027] Another object of the present invention is to provide a MOF@SAC adsorbent having a multi-level pore structure and multiple Lewis acid sites, which is prepared by the above-mentioned preparation method of the MOF@SAC adsorbent having a multi-level pore structure and multiple Lewis acid sites.

[0028] Due to the application of the above technical solution, the present invention has the following beneficial effects:

[0029] (1) The preparation method of the MOF@SAC adsorbent with a multi-level pore structure and multiple Lewis acid sites disclosed in the present invention has simple process operation, low dependence on equipment, high preparation efficiency and finished product qualification rate, is suitable for continuous large-scale production, and has high promotion and application value.

[0030] (2) The MOF@SAC adsorbent with a multi-level pore structure and multiple Lewis acid sites disclosed in the present invention has an extremely high specific surface area and a rich pore structure. These pores provide a large number of adsorption sites for gas molecules, thereby increasing the adsorption capacity of NH3. The combination of MOF and spherical activated carbon prepared by calcining ultra-high cross-linked resin further optimizes the pore structure of the composite material, forming a multi-level pore system of micropores, mesopores and macropores, thereby greatly increasing the diffusion and adsorption rate of gas molecules.

[0031] (3) The MOF@SAC adsorbent with a multi-level pore structure and multiple Lewis acid sites disclosed in the present invention, metal ions (such as Zn 2+ 、Zr 4+ and Fe 3+ etc.) as Lewis acidic centers, which interact strongly with NH3 and effectively enhance the adsorption efficiency. BRIEF DESCRIPTION OF THE DRAWINGS

[0032] Figure 1 The XRD patterns of the products prepared in Examples 1-3 of the present invention are shown below. DETAILED DESCRIPTION

[0033] In order to enable those skilled in the art to better understand the present invention, the technical solutions in the embodiments of the present invention will be clearly and completely described below in conjunction with the embodiments. Obviously, the described embodiments are only embodiments of a part of the present invention, rather than all embodiments. Based on the embodiments of the present invention, all other embodiments obtained under the premise of equivalent changes and modifications made by ordinary technicians in the field should belong to the scope of protection of the present invention.

[0034] In the description of the present invention, it should be understood that the instruments, equipment or devices involved are all conventional instruments, equipment or devices unless otherwise specified; the raw materials or compounds involved are all commercially available conventional raw materials or compounds unless otherwise specified; the methods involved are all conventional methods unless otherwise specified.

[0035] Example 1

[0036] A method for preparing a MOF@SAC adsorbent having a hierarchical pore structure and multiple Lewis acid sites comprises the following steps:

[0037] 1. HPS preparation

[0038] 150 g of PS microspheres were weighed as precursor resins and immersed in 300 mL of dichloromethane (DCM) for 12 h to ensure sufficient swelling; then, 50 g of AlCl3 was added in batches under magnetic stirring at 800 rpm in an ice-water bath, and the reaction was maintained in the ice bath for 8 h while stirring; after the reaction was completed, it was repeatedly washed with DCM until the effluent became clear, then extracted with ethanol for 12 h, and finally washed with deionized water until neutral to obtain ultra-high cross-linked styrene resin (HPS-DEM); the obtained HPS-DEM was added to 300 mL of trichloromethane (TCM) and swelled for 12 h, and the remaining steps were repeated to prepare HPS-DEM-TCM, which was simply referred to as HPS.

[0039] 2. SAC preparation

[0040] Weigh 150 g of the HPS prepared above and move it into a tubular furnace for high-temperature heat treatment; first, under the protection of N2, raise the temperature to 300°C at a rate of 7.5°C / min and maintain it at this temperature for 1.2 h; then raise the temperature to 450°C at a rate of 10°C / min and maintain it at this temperature for 2 h; then raise the temperature to 600°C at a rate of 12.5°C / min and maintain it at this temperature for 4 h to ensure complete carbonization, and finally naturally cool it to room temperature to prepare spherical activated carbon (SAC).

[0041] 3. Preparation of MOF@SAC

[0042] (1) Preparation of functionalized ligands

[0043] First, 29.90 g of terephthalic acid (H2BDC) and 60 mL of concentrated sulfuric acid were added to a three-necked flask and reacted for 8 h under magnetic stirring; then, the reaction solution was slowly poured into 450 mL of ice-water mixture to allow the product to precipitate; finally, the product was collected by vacuum filtration and washed alternately with ethanol and deionized water for 3 times to remove excess acid to obtain H2BDC-SO3H.

[0044] (2) MOF in situ growth

[0045] First, 8.93 g of Zn(NO3)2·6H2O was weighed and dissolved in 200 mL of anhydrous ethanol under magnetic stirring to obtain a metal salt solution; then 44.50 g of H2BDC-SO3H was weighed and dissolved in 200 mL of anhydrous ethanol under magnetic stirring to obtain a ligand solution; then, 60 g of SAC was weighed and evenly dispersed in the above-mentioned metal salt solution under magnetic stirring; next, under the action of magnetic stirring, the ligand solution was slowly added, and an appropriate amount of hydrogen chloride was added to adjust the pH value to 3-4, and the reaction was carried out at 60°C for 12 hours; finally, MOF-5 modified spherical activated carbon (MOF-5@SAC) was obtained after washing and drying.

[0046] Example 2

[0047] A method for preparing a MOF@SAC adsorbent having a hierarchical pore structure and multiple Lewis acid sites is basically the same as that of Example 1, except that 8.93 g of Zn(NO3)2·6H2O in step 3(2) is replaced by 6.99 g of ZrCl4, and the mixture is reacted at 80°C for 12 h to finally prepare UiO-66@SAC.

[0048] Example 3

[0049] A method for preparing a MOF@SAC adsorbent having a hierarchical pore structure and multiple Lewis acid sites is basically the same as that in Example 1, except that 8.93 g of Zn(NO3)2·6H2O in step 3(2) is replaced by 12.09 g of Fe(NO3)3·9H2O, the pH value is adjusted to 1-2, and the reaction is carried out at 120°C for 16 h to finally prepare MIL-53(Fe)@SAC.

[0050] Structural characterization and performance testing:

[0051] 1.XRD test

[0052] Figure 1 The XRD patterns of the three MOF@SAC samples prepared in Examples 1-3 are shown. The diffraction patterns of each sample show specific diffraction peaks corresponding to the crystal structure of the respective MOF, proving that the crystallinity of MOF is maintained and successfully grown on the spherical activated carbon support.

[0053] 2.BET and NH3 adsorption performance test

[0054] (1) Analytical testing: The BET surface area and pore structure of the material were tested by gas adsorption testing at -195 °C using a Belsorp MAXⅡ analyzer using N2 adsorption and desorption. The total surface area was determined using the Brunauer-Emmett-Taylor (BET) equation.

[0055] (2) NH3 adsorption performance test: The material was tested for gas (NH3) adsorption using the UTEST static adsorption device. Initial efficiency: Control test air volume (12L / min), test resistance (100Pa), test concentration (600ppb); Pollutant holding capacity: Control test air volume (15L / min), test resistance (100Pa), test concentration (10ppm).

[0056] The results show that the three groups of samples have high specific surface areas, and the mass adsorption ratio of NH3 is greater than 3%, among which UiO-66@SAC has the highest mass adsorption ratio, which may be related to the Zr 4+ Theoretically, the higher the charge density, the stronger the acidity of the metal ion.

[0057] Table 1 BET and NH3 adsorption properties of different resin samples

[0058] sample <![CDATA[BET(m 2 / g)]]> Initial efficiency (%) Mass adsorption ratio (%) Example 1 1764 94.3 3.22 Example 2 1374 95.7 3.49 Example 3 1024 92.0 3.06

[0059] The above embodiments are only for illustrating the technical concept and features of the present invention, and their purpose is to enable people familiar with this technology to understand the contents of the present invention and implement them accordingly. They cannot be used to limit the protection scope of the present invention. All equivalent changes or modifications made according to the spirit of the present invention should be included in the protection scope of the present invention.

Claims

1. A method for preparing a MOF@SAC adsorbent having a hierarchical pore structure and multiple Lewis acid sites, characterized in that: The steps include: Step S1, preparation of ultra-high cross-linked styrene resin: using polystyrene microspheres as a precursor resin, immersing them in polychlorinated alkanes for 6-24 hours; then, adding a catalyst in batches under magnetic stirring at 300-1000 rpm in an ice-water bath, and maintaining stirring in the ice bath for 4-12 hours; after the reaction is completed, repeatedly washing with dichloromethane until the effluent becomes clear, then extracting with an organic solvent for 6-18 hours, and finally washing with deionized water until the eluent is neutral, to obtain an ultra-high cross-linked styrene resin; Step S2, preparation of spherical activated carbon: moving the ultra-high cross-linked styrene resin prepared in step S1 into a tubular furnace for high-temperature heat treatment to obtain spherical activated carbon; Step S3, preparation of functionalized ligand: first, add organic ligand and sulfonation reagent into a three-necked flask, and react for 4-12 hours under magnetic stirring; then, slowly pour the reaction solution into a mixture of ice and water to allow the product to precipitate; finally, collect the product by vacuum filtration, and wash it alternately with ethanol and deionized water for 3 times to remove excess acid to obtain a functionalized ligand; Step S4, in-situ growth of MOF: First, weigh the metal salt, dissolve it in an organic solvent under magnetic stirring to obtain a metal salt solution; then weigh the functional organic ligand prepared in step S3, dissolve it in an organic solvent under magnetic stirring to obtain a ligand solution; then, the spherical activated carbon prepared in step S2 is uniformly dispersed in the above-mentioned metal salt solution under magnetic stirring; next, under the action of magnetic stirring, slowly add the ligand solution, add a nucleating agent, and react at 60-240°C for 2-36h; finally, after washing and drying, MOF-modified spherical activated carbon MOF@SAC is obtained.

2. The method for preparing the MOF@SAC adsorbent having a multi-level pore structure and multiple Lewis acid sites according to claim 1, characterized in that: The amount ratio of the polystyrene microspheres, polychlorinated alkanes and catalyst in step S1 is (20-150) g: (100-600) mL: (10-60) g; the polychlorinated alkanes in step S1 are one or more of dichloromethane, chloroform and 1,2-dichloroethane.

3. The method for preparing the MOF@SAC adsorbent having a multi-level pore structure and multiple Lewis acid sites according to claim 1, characterized in that: The catalyst in step S1 is one or more of anhydrous AlCl3 and anhydrous FeCl3; the organic solvent in step S1 is any one of methanol, ethanol, N,N-dimethylformamide, and N-methylpyrrolidone.

4. The method for preparing the MOF@SAC adsorbent having a multi-level pore structure and multiple Lewis acid sites according to claim 1, characterized in that: The high temperature heat treatment in step S2 is specifically as follows: first, under the protection of N2, the temperature is raised to 275-340°C at a rate of 5-7.5°C / min, and maintained at this temperature for 1-1.5h; then, the temperature is raised to 400-480°C at a rate of 7.5-10°C / min, and maintained at this temperature for 2-3h; then, the temperature is raised to 575-625°C at a rate of 10-15°C / min, and maintained at this temperature for 4-6h, and finally, it is naturally cooled to room temperature.

5. The method for preparing the MOF@SAC adsorbent having a multi-level pore structure and multiple Lewis acid sites according to claim 1, characterized in that: The amount ratio of the organic ligand, the sulfonation reagent, and the ice-water mixture in step S3 is (10-50) g: (20-100) mL: (300-600) mL.

6. The method for preparing the MOF@SAC adsorbent having a multi-level pore structure and multiple Lewis acid sites according to claim 1, characterized in that: The organic ligand in step S3 is any one of terephthalic acid, 1,4-benzenedicarboxylic acid, and trimesic acid; the sulfonating agent in step S3 is any one of concentrated sulfuric acid, chlorosulfonic acid, sulfur trioxide, and fuming sulfuric acid.

7. The method for preparing the MOF@SAC adsorbent having a multi-level pore structure and multiple Lewis acid sites according to claim 1, characterized in that: The ratio of the metal salt to the organic solvent in the metal salt solution in step S4 is (2-20) g: (50-250) mL; the ratio of the functional organic ligand to the organic solvent in the ligand solution in step S4 is (10-80) g: (50-250) mL.

8. The method for preparing the MOF@SAC adsorbent having a multi-level pore structure and multiple Lewis acid sites according to claim 1, characterized in that: The mass ratio of the metal salt, the functional organic ligand, the spherical activated carbon and the nucleating agent in step S4 is (2-20): (10-80): (20-100): (0-5); the metal salt in step S4 is any one of zinc salt, cobalt salt, copper salt, iron salt, titanium salt, aluminum salt and zirconium tetrachloride; the zinc salt is any one of Zn(NO3)2·6H2O, ZnSO4·7H2O and Zn(CH3COO)2·2H2O; the cobalt salt is Co(NO3)2·6 H2O, CoSO4·7H2O, CoCl2·6H2O; the copper salt is any one of Cu(NO3)2·3H2O, CuCl2, Cu(CH3COO)2·H2O; the iron salt is any one of Fe(NO3)3·9H2O, FeCl3·6H2O); the titanium salt is any one of TiCl4, TiOCl2; the aluminum salt is any one of Al(NO3)3·9H2O, AlCl3.

9. The method for preparing the MOF@SAC adsorbent having a multi-level pore structure and multiple Lewis acid sites according to claim 1, characterized in that: The nucleating agent in step S4 is one or more of hydrogen chloride, sodium hydroxide, polyvinyl alcohol, sodium dodecylbenzene sulfonate, and polyvinyl pyrrolidone; the organic solvent in step S4 is any one of deionized water, methanol, ethanol, N,N-dimethylformamide, and N,N-dimethylacetamide.

10. A MOF@SAC adsorbent having a multi-level pore structure and multiple Lewis acid sites, prepared by the method for preparing a MOF@SAC adsorbent having a multi-level pore structure and multiple Lewis acid sites according to any one of claims 1 to 9.

Citation Information

Patent Citations

  • A highly efficient modified activated carbon capable of adsorbing multiple VOC gases and its preparation method

    CN111533127B

  • Metal organic framework material of Cu, preparation method and ammonia gas adsorption application

    CN118185037A